Roles of sodium hydrogen exchanger (NHE1) and anion exchanger (AE2) across chondrocytes plasma membrane during longitudinal bone growth - Abdul Abubakar, Adamu; Ali, Ahmed Khalaf; Mohammed Ibrahim, Sahar; Handool, Kareem Obayes; Khan, Mohammad Shuaib; Mohamed Mustapha, Noordin; Tengku Ibrahim, Tengku Azmi; Kaka, Ubedullah; Mohamad Yusof, Loqman (MDPI, 2022)
Mammalian long bone growth occurs through endochondral ossification, majorly regulated by the controlled enlargement of chondrocytes at the growth plate (GP). This study aimed to investigate the roles of Na+/H+ (sodium hydrogen exchanger (NHE1)) and HCO3− (anion exchanger [AE2]) during longitudinal bone growth in mammals. Bones from P10 SpragueDawley rat pups were cultured exvivo in the presence or absence of NHE1 and AE2 inhibitors to determine their effect on long bone growth. Gross morphometry, histomorphometry, and immunohistochemistry were used to assess the bone growth. The results revealed that the culture of the bones in the presence of NHE1 and AE2 inhibitors reduces bone growth significantly (p < 0.05) by approximately 11%. The inhibitor significantly (p < 0.05) reduces bone growth velocity and the length of the hypertrophic chondrocyte zone without any effect on the total GP length. The total GP chondrocyte density was significantly (p < 0.05) reduced, but hypertrophic chondrocyte densities remained constant. NHE1 fluorescence signaling across the GP length was higher than AE2, and their localization was significantly (p < 0.05) inhibited at the hypertrophic chondrocytes zone. The GP lengthening was majorly driven by an increase in the overall GP chondrocyte and hypertrophic chondrocyte densities apart from the regulatory volume phenomenon. This may suggest that NHE1 and AE2 could have a regulatory role in long bone growth.